Towards ethnic identity and ethnic consciousness: Perceptions of minority groups towards social integration - Ngeow, Y.M.; Ngeow, K.Y.H. (2010)
This study provides insights into how a Chinese minority in a Malay-dominated community is situated at the crossroad, having to choose between two spectrums of Islamic governance. In this ethnography study that focused on ethnic Chinese minority’s perceptions, the authors raised discussions on social integration and expanded on the understanding of “functional” ethnic identity and a critical level of ethnic consciousness that serve to enhance social integration in a pluralistic society. Keywords: ethnic identity, ethnic consciousness, minority group, Islamisation governance, social integration